2021
DOI: 10.1016/j.clnesp.2021.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring nutrition therapy amid the COVID-19 pandemic: Does it work?

Abstract: Background: The COVID-19 pandemic has been a challenge for nutrition monitoring and delivery. This study evaluates clinical and nutritional characteristics of patients infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and investigates the relationship between nutrition delivery and clinical outcomes. Methods: Prospective observational study of adults admitted for >24 hrs to a tertiary-care hospital during a period of 2months. Data was collected on disease severity, energy, protein deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…In one study from China, patients were transferred from other hospitals to the study hospital; thus, the overall severity of COVID-19 was very high and, additionally, only patients over 65 years were included, both contributing to more NRS 2002 points [17]. In our analysis, the nutritional risk expressed by the NRS 2002 was associated with a higher risk of in-hospital mortality, which was already shown in a study with patients hospitalized in a medical ward and ICU with COVID-19 [32] and in a cohort of severely and critically ill patients with COVID-19 [18]. However, these associations are not only COVID-19-specific, but generally true for medical inpatients with and without infections [33,34].…”
Section: Discussionsupporting
confidence: 56%
“…In one study from China, patients were transferred from other hospitals to the study hospital; thus, the overall severity of COVID-19 was very high and, additionally, only patients over 65 years were included, both contributing to more NRS 2002 points [17]. In our analysis, the nutritional risk expressed by the NRS 2002 was associated with a higher risk of in-hospital mortality, which was already shown in a study with patients hospitalized in a medical ward and ICU with COVID-19 [32] and in a cohort of severely and critically ill patients with COVID-19 [18]. However, these associations are not only COVID-19-specific, but generally true for medical inpatients with and without infections [33,34].…”
Section: Discussionsupporting
confidence: 56%
“…In a Brazilian ICU cohort, protein provision above 0.8 g/Ideal Body Weight/day was also associated with lower mortality [107]. A protective impact was also reported in a mixed cohort of non-ICU and ICU patients [108] for reaching overall adequacy of calorie and protein provision at 25 kcal and 1.2e1.5 g per kg/day, respectively. Conversely, in a study from the United States, intolerance to enteral nutrition in ICU was associated with nutritional complications including higher risk of malnutrition, higher risk of organ failure and overall mortality [109].…”
Section: Benefits: Acute Setting (Hospital and Icu)mentioning
confidence: 56%
“…Another study of 139 COVID-19 inpatients demonstrated that those with malnutrition were more likely to be hospitalised longer compared with those of normal nutritional status, by about 11 days on average [7]. A prospective study of 183 COVID-19 patients admitted to ICU in Italy found that 76% survived when calorie adequacy was >80% compared to 33% survival when it was <80% [8]. Furthermore, another Italian study assessing ward-based COVID-19 patients found that deaths in the patients who were meeting their energy and protein needs were reported less frequently than those who were not, with an overall mortality rate of 7.1% vs. 36.8%, n ¼ 94, although this was not adjusted for potential confounding variables [9].…”
Section: Introductionmentioning
confidence: 99%